Alteration in haematological, biochemical and reproductive indices of Rattus norvegicus treated with lambdacyhalothrin. Issue 1 (2nd January 2016) - Yekeen, Taofeek Akangbe; Fawole, Olatunde Olubanjo; Bakare, Adekunle A.; Emikpe, Ben O.
Abstract: Lambdacyhalothrin (LCT), a type II pyrethroid pesticide, is an efficacious pesticide. Its use in the environment has increased tremendously. Acute and chronic toxic effects of LCT were evaluated in male Rattus norvegicus . Lethal doses (LD) were determined and chronic effects on haematological and biochemical indices, sperm count, motility and morphology and histology of testes were evaluated using 5, 10, 20 and 40% of 96 h LD50 . The 96 h LD50 value obtained for treated rats was 9.625 mg/kg bw. A significant reduction in values of packed cell volume, haemoglobin and red blood cell count was observed. Marked effects on haematological indices were at 1.925 and 3.850 mg/kg bw as the period of evaluation increased. Increase in mean cell volume and mean cell haemoglobin with slight variations in rats treated with 1.925 and 3.850 mg/kg bw indicates macrocytic anaemia. Increased serum glucose and cholesterol levels were observed, while a significant reduction in total protein and globulin was dose-dependent. A significant reduction ( p  < 0.05) in sperm count, severe testicular degeneration (at 1.925 and 3.850 mg/kg bw) and increase in aberrant sperm cells at 0.963 and 3.850 mg/kg bw were observed. Inductions of aberrations in treated rats showed the mutagenic potential of LCT. A long-term exposure to this pesticide caused abnormalities and might have reduced the life span of non-target organisms. The outcome of this study will assist in future ecotoxicological evaluations.